Body composition and physical performance of Slovak Ice hockey players with different training approach during pre-season preparation - Čerňanová Veronika Candráková; Čerňan Ján; Danková Zuzana; Siváková Daniela (Anthropological Review, 2018)
The pre-season preparation aim is to improve the components of physical performance through the changes in training intensity, gradual increment in volume, variation in training frequency and optimizing the body composition. The problem in team sports is the lack of individualization, because most coaches in team sports focus their training on the group and not on improving each player’s strengths and weaknesses. The aim of this study is to identify differences in the body composition and physical performance of young ice-hockey players (15-18 years) with different pre-season training approaches (collective vs. individual). This longitudinal study monitored 13 ice-hockey players with collective training and 8 ice-hockey players with individual training during their pre-season preparation. Body composition was measured by bioimpedance analyzer BIA 101 (Akern, S.R.L.) and the Myotest PRO determined player physical performance in power, force and velocity. Performance and body composition comparisons showed gradual increase in the differences between the two studied groups during the training process. This increase escalated to significant differences in the final output test results and was especially noted in the upper limbs power and force (p=0.016; p<0.001) and lower limbs power and force (p=0.029; p=0.001) with better performance results by individual training approach. Stepwise linear regression also showed significant relationship between upper limbs power, resistance (p<0.001) and fat mass (p<0.001). The upper limbs force was significantly associated with intra-cellular (p<0.001) and extra-cellular water (p=0.026), body cell mass index (p<0.001), basal metabolic rate (p<0.001) and training approach (p<0.001), while the lower limbs power was significantly associated with total body water (p<0.001), training approach (p=0.033) and the pre-season preparation phase (p<0.001). In addition, the training approach (p<0.001), preparation phase (p<0.001), player position (p=0.012) and fat free mass (p<0.001) were significantly associated with lowers limb force. Our results indicate the importance of using an individual training approach and optimal body composition in physical performance progression.